2020
DOI: 10.1017/cts.2019.448
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementing changes in opioid prescribing in rural primary care clinics

Abstract: Background: Opioids are more commonly prescribed for chronic pain in rural settings in the USA, yet little is known about how the rural context influences efforts to improve opioid medication management. Methods: The Six Building Blocks is an evidence-based program that guides primary care practices in making system-based improvements in managing patients using long-term opioid therapy. It was implemented at 6 rural and rural-serving organizations with 20 clinic locations over a 15-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Studies have examined provider challenges, 27 including competing time demands, 16 , 17 concerns about provider autonomy in prescribing opioids for pain, 16 and challenging conversations with patients about opioid tapering. 18 , 20 , 28 Systems-level challenges to implementing changes to opioid prescribing include challenges with existing data systems, 16 , 28 and a lack of nonpharmacological pain management resources. 19 , 29 We found similar challenges in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have examined provider challenges, 27 including competing time demands, 16 , 17 concerns about provider autonomy in prescribing opioids for pain, 16 and challenging conversations with patients about opioid tapering. 18 , 20 , 28 Systems-level challenges to implementing changes to opioid prescribing include challenges with existing data systems, 16 , 28 and a lack of nonpharmacological pain management resources. 19 , 29 We found similar challenges in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Previous studies have identified significant barriers to increasing guideline-concordant care, including inadequate time and resources, unavailability of quality data metrics, and provider and patient concerns. 16 20 …”
mentioning
confidence: 99%
“…Many studies have demonstrated the barriers faced by rural providers to safely prescribe opioids. 32 - 36 These barriers include difficulty using the PDMP during patient visits, 32 competing demands on clinicians and staff, a culture of clinician autonomy, inadequate data systems, and a lack of patient resources. 32 , 35 , 36 The COVID-19 pandemic disrupted all facets of primary care 37 and created the need for an unprecedented, rapid uptake of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“… 32 - 36 These barriers include difficulty using the PDMP during patient visits, 32 competing demands on clinicians and staff, a culture of clinician autonomy, inadequate data systems, and a lack of patient resources. 32 , 35 , 36 The COVID-19 pandemic disrupted all facets of primary care 37 and created the need for an unprecedented, rapid uptake of telemedicine. 38 Uptake of telemedicine for medication treatment for managing patients with chronic pain may be one strategy for providers in rural areas to assist patients with getting the care they need 39 ; however, the effectiveness of telemedicine has not been proven, and barriers to its use in rural areas (eg, lack of broadband), may hamper this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of patients on OAT can be complicated due to a wide range of intrinsic, extrinsic, and environmental factors, such as shortages of health care personnel, lack of technology for telehealth, failure of medication doses to meet the patient's needs, continued illicit drug use, and lack of social supports [8,[15][16][17][18][19]. Unfortunately, the premature cessation of OAT is associated with a variety of negative outcomes [20][21][22], including drug overdose, bloodborne infections, worsening substance use, and death [19,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%